Village in the sky - McDevitt, Jack (McDevitt, Jack. Alex Benedict novels., 2023)
When an entire town seemingly vanishes from a planet with conditions favorable to life, Alex Benedict and his archaeological crew must solve the mystery of how these aliens disappeared so rapidly, and why, which raises the stakes as they each look to make their mark on history.